Necessary Properties of Relevant Research: Lessons from Recent Criticisms of the Organizational Sciences - Thomas, Kenneth W.; Tymon, Walter G. (Academy of Management Review, 1982)
Kenneth W. Thomas, Walter G. Tymon, Jr., Necessary Properties of Relevant Research: Lessons from Recent Criticisms of the Organizational Sciences, The Academy of Management Review, Vol. 7, No. 3 (Jul., 1982), pp. 345-352